A longitudinal diffusion tensor MRI study of the cervical cord and brain in amyotrophic lateral sclerosis patients. Issue 1 (17th October 2008) - Agosta, F; Rocca, M A; Valsasina, P; Sala, S; Caputo, D; Perini, M; Salvi, F; Prelle, A; Filippi, M
Abstract : Objective: To define the temporal evolution of intrinsic tissue damage and atrophy in the cervical cord and the brain portion of the corticospinal tracts (CST) from patients with amyotrophic lateral sclerosis (ALS). Methods: Conventional and diffusion tensor (DT) magnetic resonance imaging (MRI) of the cervical cord and brain were obtained from 17 ALS patients and 20 controls, at baseline and after a mean follow-up of 9 months. The following measurements were assessed: (a) cervical cord cross-sectional area, average mean diffusivity (MD) and average fractional anisotropy (FA); and (b) CST T2-visible hyperintensities, average MD and FA. Results: During the follow-up, ALS patients showed a significant decrease in cord area (p = 0.003) and cord average FA (p = 0.01), and a significant increase in cord average MD (p = 0.01). In ALS patients, longitudinal changes of diffusivity measurements were not associated with cord area changes. At baseline, brain CST average MD was significantly higher in ALS patients compared with controls (p = 0.001). Brain CST diffusivity measurements remained stable over time in ALS patients and did not correlate with cord damage. Conclusions: This study shows that progressive tissue loss and injury to the remaining tissue occur in the cervical cord of ALS patients and that these two features of ALS-related pathology are not strictly interrelated. Cord pathology in ALS patients is likely to be independent of brain changes, indicating that imaging the cervical cord may be a useful adjunctive tool to monitor ALS evolution.